Uncertainty of The Substance of Article 18b in Creating Legal Norms Regarding The Determination of Special Regions in Indonesia - Achmad Daffa Meilana Rifqi; Vicko Wahyu Rifan Toyiby; Sofyan Arief (Riviera Publishing, 2025)
Special Regions are regions that have special government regulations that sometimes deviate from general regulations. The purpose of this writing is as a source of discussion. There are no regulations that regulate in detail the classification or conditions that determine why an area can be said to be a special area or a special area. In the discussion of this journal, it was also found that there was a lack of synchronization of the Legislation for Determining Special Regions with other Legislation. However, the existing law only specifically discussed the Province of the Special Region of Yogyakarta. Therefore, there is a need for a law that regulates in detail the classification and requirements regarding special areas or special areas.